Legal Protection and Justice for Franchise Business Operators from an Islamic Law Perspective - Wibowo, Agung Satryo; Hardyansah, Rommy; Darmawan , Didit; Saputra, Rio; Negara, Dharma Setiawan (Journal of Ecohumanism, 2024)
This study discusses strategies to enhance the economic well-being of the community through engagement in entrepreneurship, especially through the franchise business model. Franchising is a marketing strategy for rapidly expanding businesses through the concept of cooperation. Legal protection for franchise business operators is crucial in maintaining a balance between the parties involved. Although there are no specific verses about franchising in the Quran, the principles of business ethics, justice, and compliance with Islamic law are essential foundations that should be applied in all forms of business transactions, including franchising. This study uses an empirical juridical legal approach to explore the concept of franchising, Islamic legal principles, and the impact of legal protection on franchise business operators. The results of this research are expected to make a significant contribution to advancing the legal discourse related to franchise business and Islamic law in Indonesia.Legal protection helps franchise business operators manage risks and conduct business in accordance with the principles of justice and business ethics, from both Islamic and general legal perspectives. Islamic and general law play a crucial role in shaping a fair, orderly, and sustainable franchise business environment. With a clear and consistent framework, franchise business operators can focus on the development and growth of their businesses. Thus, legal protection serves as a strong foundation for sustainable franchise business growth in Indonesia and makes a positive contribution to the economy and society as a whole. Franchise businesses can be a suitable form of enterprise that aligns with the values and principles of Islamic economics, providing a positive contribution to the economy and society overall.